Relationship among pedal cadence, aerobic capacity and leg strength in young cyclists of different age - Volungevicius, G. (Lithuanian Academy of Physical Education, 2010)
The aim of the study was to establish interrelationship among pedal cadence, aerobic capacity and leg force in young cyclist of different age. Methods: antrophometric measurements, heart rate recording, biochemical analysis of the blood, ergometry, dynamometry, mathematical statistics. Conclusions. During increasing cycling exercise older and better trained young cyclists demonstrated higher absolute aerobic power (VO2max and ventilatory thresholds). Relative values of aerobic power parameters were similar in groups of different age. Sub maximal absolute and relative heart rate values were also similar in cyclists of different age. Pedal cadence has greater effect on aerobic capacity in junior group: the second ventilatory threshold and peak power achieved during increasing cycling decreased with increasing pedal cadence. Aerobic work efficiency was similar in both young cyclists groups and did not depend on pedal cadence. The leg force was higher in older group but at the highest velocity of contraction the difference was not significant. The correlation between force and aerobic capacity variables varied in different age groups.